Effect of On-Demand vs Routine Nebulization of Acetylcysteine With Salbutamol on Ventilator-Free Days in Intensive Care Unit Patients Receiving Invasive Ventilation: A Randomized Clinical Trial - van Meenen, David M P; van der Hoeven, Sophia M; Binnekade, Jan M; de Borgie, Corianne A J M; Merkus, Maruschka P; Bosch, Frank H; Endeman, Henrik; Haringman, Jasper J; van der Meer, Nardo J M; Moeniralam, Hazra S; Slabbekoorn, Mathilde; Muller, Marcella C A; et al. (JAMA : the journal of the American Medical Association, 2018)
It remains uncertain whether nebulization of mucolytics with bronchodilators should be applied for clinical indication or preventively in intensive care unit (ICU) patients receiving invasive ventilation. To determine if a strategy that uses nebulization for clinical indication (on-demand) is noninferior to one that uses preventive (routine) nebulization. Randomized clinical trial enrolling adult patients expected to need invasive ventilation for more than 24 hours at 7 ICUs in the Netherlands. On-demand nebulization of acetylcysteine or salbutamol (based on strict clinical indications, n = 471) or routine nebulization of acetylcysteine with salbutamol (every 6 hours until end of invasive ventilation, n = 473). The primary outcome was the number of ventilator-free days at day 28, with a noninferiority margin for a difference between groups of -0.5 days. Secondary outcomes included length of stay, mortality rates, occurrence of pulmonary complications, and adverse events. Nine hundred twenty-two patients (34% women; median age, 66 (interquartile range [IQR], 54-75 years) were enrolled and completed follow-up. At 28 days, patients in the on-demand group had a median 21 (IQR, 0-26) ventilator-free days, and patients in the routine group had a median 20 (IQR, 0-26) ventilator-free days (1-sided 95% CI, -0.00003 to ∞). There was no significant difference in length of stay or mortality, or in the proportion of patients developing pulmonary complications, between the 2 groups. Adverse events (13.8% vs 29.3%; difference, -15.5% [95% CI, -20.7% to -10.3%]; P < .001) were more frequent with routine nebulization and mainly related to tachyarrhythmia (12.5% vs 25.9%; difference, -13.4% [95% CI, -18.4% to -8.4%]; P < .001) and agitation (0.2% vs 4.3%; difference, -4.1% [95% CI, -5.9% to -2.2%]; P < .001). Among ICU patients receiving invasive ventilation who were expected to not be extubated within 24 hours, on-demand compared with routine nebulization of acetylcysteine with salbutamol did not result in an inferior number of ventilator-free days. On-demand nebulization may be a reasonable alternative to routine nebulization. clinicaltrials.gov Identifier: NCT02159196.